1897 How do Australian migrant and refugee youth navigate sexual and reproductive health decision-making? A group concept mapping study. (15th December 2022) - Napier-Raman, Sharanya; Hossain, Syeda Zakia; Mpofu, Elias; Lee, Mi-Joung; Dune, Tinashe; Liamputtong, Pranee
Abstract : Objectives: Sexual and reproductive health (SRH) is a central aspect of wellbeing, the attainment of which is a human right. Adolescents and young adults are vulnerable to compromised sexual and reproductive health and rights (SRHR). This is exacerbated in marginalised groups such as migrant and refugee youth (MRY) who navigate socioecological challenges, from communication barriers to cultural and religious clashes and conflict with family and their communities. Australian MRY have poorer SRH outcomes and service use than non-migrant youth, receive inadequate SRH education and have low SRH knowledge. Our study aims were to use the Group Concept Mapping approach to 1) identify socioecological factors that MRY perceive as influencing their SRH decision-making; and 2) understand perspectives of MRY compared with key stakeholders working in the area. Methods: Data were collected using GCM, a mixed-methods participatory approach that integrates qualitative conceptual data and multivariate statistical analyses. Participants included 1) MRY – aged 16–26 years, of migrant or refugee background, living in Western Sydney, Australia – and, 2) key stakeholders including clinicians, service providers and researchers. Snowball and purposive sampling were used. During Phase 1, 40 MRY and six stakeholders brainstormed factors influencing MRY SRH choices. During Phase 2, 42 MRY and 13 stakeholders sorted brainstormed statements into groups based on similarity. Participants rated each statement on importance, using a 5-point Likert scale; and impact, using a 3-point scale of -1, 'negative impact', to +1, 'positive impact'. We used multidimensional scaling and hierarchical cluster analysis to transform sorting and rating data into cluster concept maps. We labelled clusters based on qualitative content. Finalised maps were presented to five MRY for interpretation, and cluster labels altered according to feedback. Results: The final map contained six clusters depicting the main concepts informing MRY decision-making. Table 1 presents clusters and their ratings. Clusters 4 and 5 were most important to decision-making. Cluster 4 had the most positive impact, and Cluster 6 the most negative. Comparison of MRY and stakeholder importance ratings found overall correlation of .71, but significant difference between MRY and stakeholders for Clusters 4, t (24) = 3.0335, p = .0057, and 5, t (14) = 2.2409, p =.0418. MRY rated healthy relationships (Cluster 4) more important than stakeholders did. Conclusions: The factors that were most important and had most positive impact were 'sexual risk, safe sex practices and prevention', and 'healthy relationships, emotional security and values'. While family and cultural factors had an overall negative impact, MRY did not perceive these as highly important, suggesting MRY navigate decision-making around these restrictions. Policy and programming should go beyond biomedical disease and pregnancy prevention to incorporate emotional and social aspects of SRH, which MRY value as equally important and beneficial to their agency.